Advantages and challenges of novel materials for future space applications - Pernigoni, L.; Grande, A. M. (Frontiers in Space Technologies, 2023)
In the last years space technologies have made giant leaps, increasing the feasibility of human exploration and colonization of other celestial bodies. The Moon and Mars have become appealing in these terms, but autonomy, adaptability and high reliability are inevitably needed in long-term missions. Furthermore, new generation spacecraft will have to face challenges related to the degradation of materials and the continuous exposure to the threats of space environment. Novel materials and technologies must hence be developed to satisfy future missions requirements. This paper aims at giving a clear and organic overview of the most significant innovations in the field of materials for space applications, along with the related advantages and challenges. After introducing the main environmental factors in space and their possible risks and effects on materials, the authors proceed with the description of novel materials for space applications, subdivided into polymers, metals, semiconductors, composites, and mixtures. Innovations in manufacturing techniques and in-situ resource utilization are also briefly presented before moving to final considerations on the limitations and future challenges for these innovative materials.